Empowering the Rural Farming Community: a Case of Community Radio in Jharkhand - Rao, V. Madhava; Hermon, R R; Padhi, Rajashree; Anuradha, P (Journal of Agricultural Extension Management, 2019)
The present paper is an outcome of a detailed study based on Chala Ho GaonMein Community Radio initiative of Palamu district of Jharkhand. The studywas conducted to understand the impact of the initiative upon the rural farmingcommunity of the specified region. The objective of the paper is to highlight therole of the government in facilitating the community radio for theempowerment of the rural community 'of Palamu district of Jharkhand. Withthe new legislation of the Government of India on Community Radio, Chala HoGaon Mein Initiative became a vibrant means of information dissemination, asignificant pWorm for people's participation and a forum for expressing theirday to day grievances and resolving it locally. `Chala Ho Gaon Mein' is aunique experiment in using media technologies, especially radio, fordevelopment and empowerment of marginalised, rural communities.